Managing capital flows: The case of India - Ajay Shah; Ila Patnaik (Asian Development Bank Institute (ADBI), 2008)
From the early 1990s, India embarked on easing capital controls. Liberalization emphasized openness towards equity flows, both FDI and portfolio flows. In particular, there are few barriers in the face of portfolio equity flows. In recent years, a massive increase in the value of foreign ownership of Indian equities has come about, largely reflecting improvements in the size, liquidity and corporate governance of Indian firms. While the system of capital controls appears formidable, the de facto openness on the ground is greater than is apparent, particularly because of the substantial enlargement of the current account. These changes to capital account openness were not accompanied by commensurate monetary policy reform. The monetary policy regime has consisted essentially of a pegged exchange rate to the US dollar throughout. Increasing openness on the capital account, coupled with exchange rate pegging, has led to a substantial loss of monetary policy autonomy. The logical way forward now consists of bringing the de jure capital controls up-to-date with the de facto convertibility, and embarking on reforms of the monetary policy framework so as to shift the focus of monetary policy away from the exchange rate to domestic inflation.
Keywords: F21; F34; E42; 330; Portfolio-Investition; Kapitalverkehrspolitik; Indien